IMPLEMENTASI KEBIJAKAN MOBILE JKN DALAM MENINGKATKAN EFISIENSI RAWAT JALAN DI RSUD H. PADJONGA DAENG NGALLE KABUPATEN TAKALAR: MODEL VAN METER DAN VAN HORN - Amina; Asri; Nuryanti Mustari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the implementation of the Mobile JKN policy in improving the efficiency of outpatient services at H. Pajonga Daeng Ngalle Regional Hospital, Takalar Regency. The main problem faced is the persistence of obstacles in outpatient services even though the Mobile JKN application has been implemented, such as limited internet network in certain areas, low patient technological literacy, and dependence on staff assistance. These conditions have an impact on the efficiency of time and service flow that is not optimal. The purpose of this study is to determine and describe the implementation of the Mobile JKN policy in improving outpatient efficiency by using the Van Meter and Van Horn policy implementation model. This study uses a qualitative approach with a descriptive type. Data collection techniques were carried out through interviews, observation, and documentation with informants directly involved in the Mobile JKN service. Data analysis was carried out qualitatively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Mobile JKN policy at H. Pajonga Daeng Ngalle Regional Hospital has essentially helped improve the efficiency of outpatient services, especially in reducing queue times and regular service flow. However, the effectiveness of the implementation is not optimal because it is still influenced by limited resources, especially technological facilities, internet network quality, and public understanding of the use of the application. This study concludes that the success of Mobile JKN implementation is largely determined by the clarity of policy standards, resource readiness, implementer attitudes, and social environmental support.